Patient satisfaction with virtual evaluation, diagnosis, and treatment of CRPS. Issue 1 (31st December 2022) - Loy, Emma; Scheidler, Anna; Packham, Tara; Dow, Heather; Winston, Paul
ABSTRACT: Background: The COVID-19 pandemic has led to an increased reliance on virtual care in the rehabilitation setting for patients with conditions such as complex regional pain syndrome (CRPS). Aims: The aim of this study was to perform a quality improvement initiative to assess patient satisfaction and ensure that outcomes following virtual assessment, diagnosis, and treatment of CRPS with prednisone are safe and effective. Methods: An online survey was distributed to 18 patients with CRPS who had been seen virtually between March and December 2020 through a rehabilitation clinic and treated with oral prednisone. Thirteen participants completed the survey, which was designed de novo by our team to evaluate participant perceptions and satisfaction regarding the virtual care experience. Also included in the survey was a CRPS-specific validated patient-report questionnaire (Hamilton Inventory for CRPS: PR-HI-CRPS), which allowed participants to describe their specific symptoms and associated functional and psychosocial impacts, both previously (pretreatment baseline) and at the time of survey (posttreatment). Results: CRPS symptoms and related impacts were scored as significantly improved from baseline following treatment with prednisone. Likert scale results from survey responses related to patients' experiences and satisfaction with the virtual care process were analyzed; the majority of patients reported satisfaction with a virtual appointment for evaluation of CRPS, as well as with subsequent treatment decisions based on virtual assessment. Conclusions: This quality improvement study suggests that virtual care is a potential option for a patient-accepted approach to overcoming challenges with in-person care imposed by the COVID-19 pandemic and could help inform future considerations in addressing geographic and patient-specific disparities in access to specialist care for CRPS.